Early stages of Palaeolithic rock art in southern Iberia. Malaga area - Cantalejo Duartea, Pedro; Fernández Rodríguez, Luis-Efrén; Collado Giraldo, Hipólito; Weniger, Gerd-Christian; Espejo Herrerías, María del Mar; Fernández-Sánchez, Diego; Liñán Baena, Cristina; del Rosal Padial, Yolanda; Garcês, Sara; Gomes, Hugo; Lattao, Virginia; Nash, George; et al. (Complutum, 2025)
We present a record of caves in southern Iberia in which Palaeolithic graphic manifestations are made up of a variety of signs, among which fingerings and punctuations, traces, pigment projections on geological formations, or coloured stains applied to the surface or edges of the speleothems predominate. They have been included in the concept of ‘aniconic horizon’. The uranium series dating in Cueva de Ardales has confirmed the remarkable antiquity of some of these manifestations. We present the caves in Malaga that have evidence of these graphic representations. We provide data on the methodology of the archaeometric analyses carried out as part of the First Art Project and discuss and evaluate their chronological and cultural framework in relation to the Palaeolithic societies of the region.